Comparison of Different Mandibular Jawlines Classifications on Transoral Endoscopic Thyroidectomy for Papillary Thyroid Carcinoma: Experiences of 690 Cases - Yu, Xing; Jiang, Yuancong; Li, Yujun; He, Qionghua; Pan, Lei; Zhu, Peifeng; Wang, Yong; Wang, Ping (Frontiers in Endocrinology, 2022)
Background The influences of patients’ different mandibular jawlines on transoral endoscopic thyroidectomy via vestibular approach (TOETVA) have not been described before. The objective of this study was to introduce a new classification to assess different mandibular jawlines, and to evaluate the effects on TOETVA in terms of safety, feasibility, and postoperative feelings in the treatment of papillary thyroid carcinoma (PTC). Methods The crossing angle of esthetic plane and mandibular plane was defined as Wang Angle, used to assess patients’ different mandibular jawlines. Mandibular classifications of A (angle: 80° 110°), B (angle > 110°), and C (angle < 80°) types were compared to evaluate the surgical outcomes of TOETVA by a retrospective study. 690 patients of PTC who received TOETVA were included in this study, which were divided into three groups according to mandibular classifications. Results Clinicopathological characteristics of the patients including age, gender, body mass index, tumor size, Hashimoto thyroiditis were similar in the three groups. Patients’ length of jay in group C was significantly longer than group A and group B (P < 0.01). The ratios of using suspension system in group C were significantly higher than group A and group B (P < 0.01). The scores of postoperative visual analogue scale (VAS) and ratios of mandibular swell in group C were significantly higher than group A and group B (P < 0.01). There was no significant difference in the three groups regarding surgical outcomes, including postoperative vocal cord paralysis, hypocalcemia, serum white blood cells and C-reactive protein levels. Conclusions The Wang angle and mandibular jawline classifications were firstly introduced in TOETVA. All the patients of class A, B, and C mandibular jawline can achieve safe and effective surgical outcomes in the treatment of PTC with TOETVA. Patients of class C need more assistance of suspension system, would experience higher scores of VAS, and higher ratios of mandibular swell compared with class A and B.